Influenza vaccination among Australian Hajj pilgrims: uptake, attitudes, and barriers - Barasheed, Osamah; Rashid, Harunor; Heron, Leon; Ridda, Iman; Haworth, Elizabeth; Nguyen-Van-Tam, Jonathan S.; Dwyer, Dominic E.; Booy, Robert (Oxford University Press, 2014)
Background: Hajj is the largest annual mass gathering where the risk of respiratory infection is high. Although the Saudi Arabian authority recommends influenza vaccination for Hajj pilgrims, the uptake is variable. Influenza vaccine uptake data among Australian Hajj pilgrims is not readily available. Therefore, we aimed to estimate the influenza vaccination uptake rate and identify both attitudes and barriers to vaccine uptake from two consecutives surveys at Hajj in 2011 and 2012.